Practice guideline update summary: Vaccine-preventable infections and immunization in multiple sclerosis. (24th September 2019) - Farez, Mauricio F.; Correale, Jorge; Armstrong, Melissa J.; Rae-Grant, Alexander; Gloss, David; Donley, Diane; Holler-Managan, Yolanda; Kachuck, Norman J.; Jeffery, Douglas; Beilman, Maureen; Gronseth, Gary; Michelson, David; et al.
Abstract : Objective: To update the 2002 American Academy of Neurology (AAN) guideline regarding immunization and multiple sclerosis (MS). Methods: The panel performed a systematic review and classified articles using the AAN system. Recommendations were based on evidence, related evidence, principles of care, and inferences according to the AAN 2011 process manual, as amended. Major recommendations (Level B except where indicated): Clinicians should discuss the evidence regarding immunizations in MS with their patients and explore patients' opinions, preferences, and questions. Clinicians should recommend that patients with MS follow all local vaccine standards, unless there are specific contraindications and weigh local vaccine-preventable disease risks when counseling patients. Clinicians should recommend that patients with MS receive the influenza vaccination annually. Clinicians should counsel patients with MS about infection risks associated with specific immunosuppressive/immunomodulating (ISIM) medications and treatment-specific vaccination guidance according to prescribing information (PI) and vaccinate patients with MS as needed at least 4–6 weeks before initiating patients' ISIM therapy. Clinicians must screen for infections according to PI before initiating ISIM medications (Level A) and should treat patients testing positive for latent infections. In high-risk populations, clinicians must screen for latent infections before starting ISIM therapy even when not specifically mentioned in PI (Level A) and should consult specialists regarding treating patients who screen positive for latent infection. Clinicians should recommend against using live-attenuated vaccines in people with MS receiving ISIM therapies. Clinicians should delay vaccinating people with MS who are experiencing a relapse.